SELETIVIDADE E EFICIÊNCIA DA ASSOCIAÇÃO DOS HERBICIDAS IODOSULFURON-METHYL E FENOXAPROP-P-ETHYL EM CEREAIS DE INVERNO - KARPINSKI, RICARDO ANDRÉ KLOSTER (2016)
The research aimed to evaluate selectivity and efficiency of iodosulfuron-methyl + fenoxaprop-p-ethyl tank mixture applied isolated in post-emergence condition or in association with other herbicides in the wheat (Triticum aestivum) and barley (Hordeum vulgare) crops. Four experiments were conducted in field conditions at Guarapuava and Palmeirinha Counties, Parana State, during 2014 agricultural season. The first experiment was conducted in randomized complete blocks, in factorial scheme 13x2+2, with four replications, with the first factor constituted by 13 winter cereals cultivars and the second one, the association of iodosulfuron-methyl + fenoxaprop-p-ethyl, in doses of 6.5 + 82.5 and 7.5 + 110 g ha-1, respectively, at 2 to 3 and 5 to 6 leaves stages, besides two checks with and without weeds. Results indicated that iodosulfuron-methyl + fenoxaprop-p-ethyl associations showed selective potential for wheat, triticale and rye crops, as well as high efficiency in controlling ryegrass, radish, black oat and white oat. Other three experiments were conducted also in randomized complete blocks, with 11 treatments and five repetitions, constituted by (g ha-1): 1) iodosulfuron-methyl (6.5) fenoxaprop-p-ethyl (82.5), 3) fenoxaprop-p-ethyl + clethodim (55 + 54); 4) 2.4-D (335), 5, 6 e 7) iodosulfuron-methyl + fenoxaprop-p-ethyl (6.5 + 82.5; 6.5 + 110 and 6.5 + 165), 8) iodosulfuron-methyl + fenoxaprop-p-ethyl + clethodim (6.5 + 55 + 54), 9) iodosulfuron-methyl + fenoxaprop-p-ethyl + 2.4-D (6.5 + 110 + 335), 10) iodosulfuron-methyl + fenoxaprop-p-ethyl + clethodim + 2.4-D (6.5 + 82.5 + 72 + 335) and 11) check without weeds. Iodosulfuron-methyl + fenoxaprop-p-ethyl and iodosulfuron-methyl + fenoxaprop-p-ethyl + 2.4-D associations confirmed selectivity for wheat crop, without causing phytotoxicity and losses in grain yield and hectoliter weight. For barley crop, only iodosulfuron-methyl + fenoxaprop-p-ethyl, at doses of 6.5 + 82.5 and 6.5 + 110 g ha-1, was selectivity. Clethodim addition with iodosulfuron-methyl+fenoxaprop-p-ethyl was not selective for wheat and barley plants. Commercial formulation of iodosulfuron-methyl (Hussar®), resulted in protection for fenoxaprop-p-ethyl (Podium EW®) damage effects for the crops.